2006
DOI: 10.1161/circulationaha.105.567297
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Factor in Cardiovascular Diseases

Abstract: Abstract-Tissue factor (TF), formerly known as thromboplastin, is the key initiator of the coagulation cascade; it binds factor VIIa resulting in activation of factor IX and factor X, ultimately leading to fibrin formation. TF expression and activity can be induced in endothelial cells, vascular smooth muscle cells, and monocytes by various stimuli such as cytokines, growth factors, and biogenic amines. These mediators act through diverse signal transduction mechanisms including MAP kinases, PI3-kinase, and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
194
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 419 publications
(199 citation statements)
references
References 124 publications
(141 reference statements)
3
194
0
2
Order By: Relevance
“…Moreover, although evaluation in silico in another study did not indicate effects of the 4 investigated polymorphisms on transcription factor binding [11], gel shift experiments by Terry et al indeed demonstrated such effects of the Del-1208Ins polymorphism, providing a possible explanation for the genotypic differences in TF expression and activity [17]. An influence on local TF activity in the vessel wall may in turn modulate processes involved in atherosclerosis such as inflammation and VSMC migration and proliferation [2,9,10,[25][26][27][28][29][30], which could result in measurable differences in C-IMT as observed in this study. We cannot rule out, however, that the observed effect of A/G TF promoter haplotype on C-IMT may be explained by linkage disequilibrium with other genetic variants influencing the atherosclerotic process.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Moreover, although evaluation in silico in another study did not indicate effects of the 4 investigated polymorphisms on transcription factor binding [11], gel shift experiments by Terry et al indeed demonstrated such effects of the Del-1208Ins polymorphism, providing a possible explanation for the genotypic differences in TF expression and activity [17]. An influence on local TF activity in the vessel wall may in turn modulate processes involved in atherosclerosis such as inflammation and VSMC migration and proliferation [2,9,10,[25][26][27][28][29][30], which could result in measurable differences in C-IMT as observed in this study. We cannot rule out, however, that the observed effect of A/G TF promoter haplotype on C-IMT may be explained by linkage disequilibrium with other genetic variants influencing the atherosclerotic process.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, experimental studies in vitro and in vivo have shown involvement of TF in inflammation and VSMC migration/proliferation mediated via intracellular signalling by the TF cytoplasmic tail and/or TF:FVIIa-promoted extracellular proteolytic cascades and activation of protease-activated receptors (PARs) [2,9,10,[25][26][27][28][29][30]. The association between tertiles of TF and C-IMT, tested by multivariable linear regression analysis, was analysed in the subgroup of subjects (n = 120) who underwent plasma TF level determinations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations